2015
DOI: 10.1158/1940-6207.capr-14-0121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metformin, Buformin, and Phenformin on the Post-Initiation Stage of Chemically Induced Mammary Carcinogenesis in the Rat

Abstract: Metformin is a widely prescribed drug for the treatment of type-2 diabetes. Although epidemiological data have provided a strong rationale for investigating the potential of this biguanide for use in cancer prevention and control, uncertainty exists whether metformin should be expected to have an impact in non-diabetic patients. Furthermore, little attention has been given to the possibility that other biguanides may have anticancer activity. In this study, the effects of clinically relevant doses of metformin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 30 publications
2
23
1
Order By: Relevance
“…In contrast to our findings, a limited number of rodent studies have suggested that metformin does not affect mammary carcinogenesis (10,11). However, there are key differences in study design between our study and these previous reports that include variations in rodent age at initiation with MNU, diet, and dosage of metformin.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our findings, a limited number of rodent studies have suggested that metformin does not affect mammary carcinogenesis (10,11). However, there are key differences in study design between our study and these previous reports that include variations in rodent age at initiation with MNU, diet, and dosage of metformin.…”
Section: Discussioncontrasting
confidence: 99%
“…A number of preclinical studies of mammary carcinogenesis and in vitro studies using breast cancer cell lines are consistent with this assertion of metformin's beneficial effects (4-9). Even so, other preclinical studies of mammary carcinogenic models failed to see any effect of metformin when the animals were fed a low fat diet and exhibited no metabolic dysfunction (10,11). These conflicting reports suggest that there may be specific factors and metabolic conditions that confer a tumor's sensitivity to metformin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…57 Inherent risk connected with complex I inhibition is development of lactic acidosis. 3 It was published that more lipophilic metformin analogues, phenformin and buformin, have more potent antitumor effect, 58,59 but they are also more likely to trigger lactic acidosis. 3 Even metformin, which is considered relatively safe in this regard, may present higher risk of lactic acidosis in patients with associated condition, such as renal impairment, which increases metformin levels in plasma.…”
Section: Mitochondria-targeted Analogues Of Metforminmentioning
confidence: 99%
“…20 Interestingly, in another mammary cancer rat model, Zhu et al found that buformin notably decreased cancer incidence, multiplicity, and burden; however, these effects were not seen in rats fed with phenformin or metformin. 21 Based on these results, we propose that buformin might be a potent anti-cancer drug for treatment of cervical cancer, and we performed a series of experiments to illustrate this possibility.…”
Section: Introductionmentioning
confidence: 97%